Preparation of Nutmeg Gel and Evaluation of its Efficacy as Local Drug Delivery in Stage II Grade A Periodontitis Patients: A Prospective Interventional Study - Vazeeha Afrin Syed; AS Pavithra; Arvina Rajasekar; Rajeshkumar Shanmugam (Journal of Clinical and Diagnostic Research)
Introduction: Periodontitis is defined as a chronic inflammatory disease caused by specific microbes, which triggers the production of inflammatory mediators. This process leads to the loss of tissue structure and function. Nutmeg has been found to consist of a number of chemical components that have been linked to antioxidant, health promoting, and disease-prevention activity. Aim: To prepare nutmeg gel and to assess its anti-inflammatory, antioxidant, and cytotoxic activities, and its effectiveness as a locally delivered drug in the management of stage II grade A periodontitis. Materials and Methods: The present study was conducted in Department of Periodontics, Saveetha Dental College and Hospitals, Saveetha Institute of Medical and Technical Sciences (SIMATS), Saveetha University, Chennai, Tamil Nadu, India. A 30 mg nutmeg gel was prepared and subjected to anti-inflammatory, antioxidant, and cytotoxic assays. Followed by in-vitro analysis, 40 patients with stage II grade A periodontitis patients who reported between June 2023 and September 2023 to the Department of Periodontology were enrolled. A total of 20 patients were subjected to Scaling and Root Planing (SRP) alone (Group A - Control), and the remaining 20 patients were subjected to SRP + placement of 0.3% nutmeg gel (Group B - Test). Probing Depth (PD) and Clinical Attachment Level (CAL) were recorded at baseline and after three months. The data were analysed for statistical significance using Statistical Package for the Social Sciences (SPSS) software, version 23.0. Intergroup and intragroup comparison was done using independent t-test and paired t-test, respectively, with a p-value <0.05 considered statistically significant. Results: In vitro analysis revealed that the anti-inflammatory and antioxidant activity of nutmeg gel was comparable to the control. Also, the survival rate of nauplii fell within acceptable ranges. Followed by in-vivo analysis, in-vivo analysis was done. A total of 13 females and seven males with a mean age of 29.45±3.98 years were treated with SRP (Group A), and eight females and 12 males with a mean age of 28±3.22 years were treated with SRP along with 0.3% nutmeg gel (Group B). PD and CAL showed significant reduction from baseline to three months in test and control groups and was statistically significant (p<0.05). On intergroup comparison in terms of PD and CAL statistically significant difference was present (p<0.05) at the end of three months, favouring Group B. Conclusion: The developed nutmeg gel was found to be effective when used in addition to SRP as a Local Drug (LD) among patients with stage II grade A periodontitis.